Teachers training and pedagogical model at the Universidad Pedagógica y Tecnológica de Colombia - Soto Arango, Diana Elvira; Mora García, José Pascual; Lima Jardilino, José Rubens (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2017)
The pedagogical model of The Science Education Faculty is conceived at the Universidad Pedagógica y Tecnológica de Colombia on the humanistic approach, proposed since its inception with the direct antecedent of the Teacher college, originally named; Superior Normal School, in Colombia. The focus on the educational approach and the pedagogical models that underlie the faculty are established from the social history of education method, the imaginaries, and the qualitative analysis. It is concluded that the humanistic educational approach changed from Catholic to critical and keeps the principle of the integrality of the human being. An approximation to the current cognitive trend, located in the school of epistemological thought and leaned towards socio-critical models within an ethical code of principles, which are framed in the identity of the professional performance of the educator. It is proposed, in the approach to the critical pedagogical model, a balanced triad where the educator and the learner reach the focal point in the act of knowledge, this under the principle of dialogicity and mediated by social responsibility, emancipatory pedagogy and the happiness of the human being in the construction of peace in Colombia.